Experimental investigation and thermodynamic calculation of Ti-Hf-Mn system. (September 2020) - Hu, T.; Huang, X.M.; Li, J.H.; Zhang, J.; Cai, G.M.; Jin, Z.P.
Abstract: The phase relationship of Ti-Hf-Mn system was studied by diffusion triple and equilibrated alloy methods. The isothermal sections at 1373, 1273 and 1173 K for this system were constructed by means of electron probe microanalysis (EPMA) and X-ray diffraction (XRD) for the first time. No ternary phase was found in the system at all these temperatures. Six, seven and seven three-phase equilibria regions have been determined at 1373, 1273 and 1174 K, respectively. In this ternary system, the intermetallic compounds TiMn2, HfMn2 and HfMn exhibit wide solid solution range at those three temperatures. In particular, the solution range of Ti in HfMn phase decreases with the increase of temperature, from 30.5 at% at 1173 K to 26.5 at% at 1373 K. Based on all available experimental data, the Ti-Hf-Mn system was evaluated using the CALPHAD method. The calculation results are in excellent agreement with the experimental data. Graphical abstract: Image 1 Highlights: 1373, 1273 and 1173 K isothermal sections of Ti-Hf-Mn system were first established over the whole composition range. The solid solubility of Ti in HfMn phase was up to 20.6 at. % at 1373 K. The continuous solid solution of (Ti, Hf)Mn2 phase was confirmed at three different temperatures. The thermodynamics data were built and optimized for this system.